Perioperative Inflammatory Response and Cancer Recurrence in Lung Cancer Surgery: A Narrative Review - Choi, Hoon; Hwang, Wonjung (Frontiers in Surgery, 2022)
While surgical resection is the gold standard treatment for solid tumors, cancer recurrence after surgery is common. Immunosurveillance of remnant tumor cells is an important protective mechanism. Therefore, maintenance of anti-tumor cell activity and proper levels of inflammatory mediators is crucial. An increasing body of evidence suggests that surgery itself and perioperative interventions could affect these pathophysiological responses. Various factors, such as the extent of tissue injury, perioperative medications such as anesthetics and analgesics, and perioperative management including transfusions and methods of mechanical ventilation, modulate the inflammatory response in lung cancer surgery. This narrative review summarizes the pathophysiological mechanisms involved in cancer recurrence after surgery and perioperative management related to cancer recurrence after lung cancer surgery.